Pengukuran omega-3 pada ikan penja (Awaous sp.) asal Polewali Mandar Provinsi Sulawesi Barat - Rusman Hasanuddin; Nur Alim; Karnidayanti Karnidayanti (Universitas Mataram, 2023)
Omega-3 is an essential fatty acid necessary for human health. It has anti-inflammatory properties, reduces the risk of cardiovascular disease, and is needed for brain development. The three main omega-3 fatty acids are alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA). Penja fish is a typical marine biota of Polewali Mandar, West Sulawesi, which is believed to be rich in omega-3. The research aimed to determine the omega-3 content in penja fish (Awaous sp.) from Polewali Mandar, West Sulawesi Province. Penja fish was extracted using the Soxhlet method, and then the fatty acid content was analyzed by GC-MS. The results of this study show that penja fish extract (Awaous sp.) contains omega-3 consisting of 2.64% linolenic acid, 0.94% eicosapentaenoic acid (EPA), and 1.17% docosahexaenoic acid (DHA). The total omega-3 content in penja fish (Awaous sp.) is 4.75%.